Individual risk factors for hip osteoarthritis: obesity, hip injury, and physical activity. - Cooper, C; Inskip, H; Croft, P; Campbell, L; Smith, G; McLaren, M; Coggon, D (1998)
Hip osteoarthritis is a major cause of pain and disability. The authors explored individual risk factors for hip osteoarthritis in a population-based case-control study. The study was performed in two English health districts (Portsmouth and North Staffordshire) from 1993 to 1995. A total of 611 patients (210 men and 401 women) listed for hip replacement because of osteoarthritis over an 18-month period were compared with an equal number of controls selected from the general population and individually matched for age, sex, and family practitioner. Information about suspected risk factors was obtained by a questionnaire administered at interview and a short physical examination. Obesity (odds ratio (OR) = 1.7, 95% confidence interval (CI) 1.3-2.4; highest vs. lowest third of body mass index), previous hip injury (OR = 4.3, 95% CI 2.2-8.4), and the presence of Heberden's nodes (OR = 1.6, 95% CI 1.2-2.2) were independent risk factors for hip osteoarthritis among men and women. Hip injury was more closely related to unilateral as compared with bilateral disease. There were a negative association between cigarette smoking and osteoarthritis among men and a weak positive association with prolonged regular sporting activity. Obesity and hip injury are important independent risk factors for hip osteoarthritis, which might be amenable to primary prevention. Hip osteoarthritis may also arise as part of the polyarticular involvement found in generalized osteoarthritis.